Economic Strengthening Through Technological Innovation in the Processing of Fried Shallot (Allium cepa L.) at UMKM Sri Rejeki in Kedungdalem, Probolinggo - Ramadhani Mahendra Kusuma; Roziana Febrianita; Yanda Bara Kusuma; Dwi Wahyuningtyas (Universitas Muhammadiyah Malang, 2025)
This community service projects play a crucial role in addressing local economic challenges and fostering sustainable development. By focusing on agricultural enterprises, these projects can enhance productivity and improve livelihoods in rural areas, contributing to broader economic and social goals. UMKM Sri Rejeki, a fried shallot enterprise in Kedung Dalem Village, Probolinggo, faced significant challenges including declining shallot yields, reliance on labor-intensive manual processing methods, and lack of technological innovation. These issues negatively impacted production efficiency, product quality, and overall market competitiveness. This project aimed to strengthen the local economy and support UMKM Sri Rejeki by providing advanced technological solutions and training to improve production processes. The goal was to enhance efficiency, product quality, and sustainability in the shallot processing industry. The methodology encompassed direct implementation, hands-on training, and continuous mentoring. The introduction of automated machinery significantly increased production efficiency and product consistency while reducing labor costs. The training program successfully equipped operators with the necessary skills for effective machinery use and maintenance. Additionally, educational efforts on sustainable cultivation practices led to improved crop quality and reduced environmental impact. The project’s outcomes have substantial implications for the local agricultural economy. Enhanced production capabilities and sustainable practices contribute to the economic empowerment of small enterprises and promote long-term viability. By disseminating results and best practices, the project encourages broader adoption of innovative technologies and sustainable farming methods, fostering regional economic development and resilience.